Answer:
Two questions:
Question 1:
given
.
Answer 1: ![f^{-1}(x)=\frac{2}{x+3}](https://tex.z-dn.net/?f=f%5E%7B-1%7D%28x%29%3D%5Cfrac%7B2%7D%7Bx%2B3%7D)
Question 2:
given
.
Answer 2: ![f^{-1}(x)=\frac{2}{x}+3](https://tex.z-dn.net/?f=f%5E%7B-1%7D%28x%29%3D%5Cfrac%7B2%7D%7Bx%7D%2B3)
Step-by-step explanation:
So
is used in most classes to represent the inverse function of
.
The inverse when graphed is a reflection through the y=x line. The ordered pairs
on
implies
are on
.
This means we really just need to swap x and y.
Since we want to write as a function of x we will need to solve for y again.
Question 1:
![y=\frac{2}{x}-3](https://tex.z-dn.net/?f=y%3D%5Cfrac%7B2%7D%7Bx%7D-3)
Swap x and y:
![x=\frac{2}{y}-3](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B2%7D%7By%7D-3)
We want to solve for y.
Add 3 on both sides:
![x+3=\frac{2}{y}](https://tex.z-dn.net/?f=x%2B3%3D%5Cfrac%7B2%7D%7By%7D)
Make the left hand side a fraction so we can cross-multiply:
![\frac{x+3}{1}=\frac{2}{y}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%2B3%7D%7B1%7D%3D%5Cfrac%7B2%7D%7By%7D)
Cross multiply:
![y(x+3)=1(2)](https://tex.z-dn.net/?f=y%28x%2B3%29%3D1%282%29)
Simplify right hand side:
![y(x+3)=2](https://tex.z-dn.net/?f=y%28x%2B3%29%3D2)
Divide both sides by (x+3):
![y=\frac{2}{x+3}](https://tex.z-dn.net/?f=y%3D%5Cfrac%7B2%7D%7Bx%2B3%7D)
So
.
Question 2:
![y=\frac{2}{x-3}](https://tex.z-dn.net/?f=y%3D%5Cfrac%7B2%7D%7Bx-3%7D)
Swap x and y:
![x=\frac{2}{y-3}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B2%7D%7By-3%7D)
Make left hand side a fraction so we can cross multiply:
![\frac{x}{1}=\frac{2}{y-3}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%7D%7B1%7D%3D%5Cfrac%7B2%7D%7By-3%7D)
Cross multiply:
![(y-3)x=1(2)](https://tex.z-dn.net/?f=%28y-3%29x%3D1%282%29)
We have to distribute here:
![yx-3x=2](https://tex.z-dn.net/?f=yx-3x%3D2)
Add 3x on both sides:
![yx=2+3x](https://tex.z-dn.net/?f=yx%3D2%2B3x)
Divide boht sides by x:
![y=\frac{2+3x}{x}](https://tex.z-dn.net/?f=y%3D%5Cfrac%7B2%2B3x%7D%7Bx%7D)
You could probably stop here but you could also simplify a little.
Separate the fraction into two terms since you have 2 terms on top bottom being dividing by x:
![y=\frac{2}{x}+\frac{3x}{x}](https://tex.z-dn.net/?f=y%3D%5Cfrac%7B2%7D%7Bx%7D%2B%5Cfrac%7B3x%7D%7Bx%7D)
Simplify second fraction x/x=1:
![y=\frac{2}{x}+3](https://tex.z-dn.net/?f=y%3D%5Cfrac%7B2%7D%7Bx%7D%2B3)
So
.